Liposomal β-Sitosterol Suppresses Metastasis of CT26/luc Colon Carcinoma via Inhibition of MMP-9 and Evoke of Immune System - Chao-Yu Shen; Chia-Fen Lee; Wei-Taur Chou; Jeng-Jong Hwang; Yeu-Sheng Tyan; Hui-Yen Chuang (MDPI AG, 2022)
β-sitosterol (SITO) has been reported with anticancer effects; however, with poor bioavailability. The current study aimed to investigate whether liposomal encapsulated β-sitosterol (LS) has a better inhibition effect on tumor metastasis than β-sitosterol in a CT26/luc lung metastasis mouse model and the possible underlying mechanism. LS was liposomal-encapsulated SITO and was delivered to mice by oral gavage. The cell viability was determined by the MTT assay, and invasiveness of the tumor cells and related protein expression were evaluated with the invasion assay and Western blotting. For therapeutic efficacy evaluation, male BALB/c mice were treated with PBS, SITO, and LS once a day for 7 days prior to intravenous injections of CT26/luc cells; treatments were continued twice a week post-cell inoculation throughout the entire experiment. Tumor growth inhibition was monitored by bioluminescent imaging (BLI). IL-12, IL-18, and IFN-γ in the intestinal epithelium were determined by ELISA. The results show that LS treatment had a better invasion inhibition with lower cytotoxicity than SITO when the same dose was utilized. Notably, mice treated with LS significantly exhibited fewer metastases to the lungs and other tissues/organs compared with the Control and SITO groups. Additionally, the IL-12, IL-18, and IFN-γ levels were significantly increased in the LS-treated mice compared with the Control and SITO groups. The underlying mechanism may be through the inhibition of MMP-9 and elicitation of the antitumoral Th1 immune response, such as increasing CD4+ and CD8+ T cells, IL-12, IL-18, and IFN-γ.